First general report - Shortt, Edward; Nethersole, Olga, 1870-1951 (London : People's League of Health)
1922-05 1922 1920s 55 pages : illustrations MODEL SHOWING CONTRAST IN DEVELOPMENT OF CHILDREN OF AVERAGE AGE LIVING IN HOMES CONSISTING OF ONE ROOM TWO ROOMS THREE ROOMS [illustration] COMPARISON OF MALE CHILDREN ACCORDING TO SIZE OF HOUSE. PERCENTAGES. DEATH RATES SIZE OF HOUSE IN ROOMS MEAN HEIGHT IN INCHES MEAN WEIGHT POUNDS STATE of NUTRITION MENTAL CAPACITY TEACHERS ESTIMATE STOUT MEDIUM THIN EXCELLENT GOOD MEDIUM DULL 33 1 47.7 52.9 80.0 20.0 6.6 26.6 26.6 ? 21 2 49.3 56.8 4.9 77.2 14.9 16.6 45.4 31.2 6.6 11 3 50.8 59.6 10.5 74.5 14.9 17.5 49.1 28.0 5.2 8 200/B/3/2/C693/1/71